Polymer electrolyte system based on carrageenan-poly(3,4-ethylenedioxythiophene) (PEDOT) composite for dye sensitized solar cell - Ng, C. A. (Animo Repository, 2015)
Poly(3,4-ethylenedioxythiophene) (PEDOT)-κ-carregeenan polymer electrolyte blend was prepared and incorporated as the electrolyte system in dye-sensitized solar cells (DSSC). Polymer blends prepared with different κ-carrageenan concentrations and molecular weights were investigated. It was found that the conductivity of the polymer blend increases with higher κ-carrageenan concentration, and lowers with degraded κ-carregeenan. The polymer blend was incorporated in a DSSC and yielded a solar cell with efficiency (η) of 0.421%.